SAT0200 Clinical Application of the Soluble Lectin-Like Oxidized LDL Receptor-1 (SLOX-1) in Rheumatoid Arthritis: from Bench to Bedside. (10th June 2014) - Ishikawa, M.; Ito, H.; Furu, M.; Hashimoto, M.; Fuji, T.; Matsuda, S.; Mimori, T.
Abstract : Background: Previously, we have reported that levels of sLOX-1 (soluble Lectin-like oxidized LDL receptor 1) in the plasma of RA patients were significantly higher than those in healthy controls, and the anti-cytokine therapies decreased the sLOX-1 level in plasma. Objectives: Then, we investigated whether sLOX-1 levels are associated with RA disease activity or remission using a cohort study Methods: The study examined 278 RA patients (female 84.9%) in the cohort. Levels of sLOX-1 in plasma were measured by ELISA. To evaluate the correlation with sLOX-1, VAS, CRP, ESR, MMP-3, autoantibody status, the number of swollen and tender joints, DAS-ESR, SDAI, and Boolean-based remission were measured in all patients. Results: The levels of sLOX-1 in RF-positive or ACPA-positive RA were significantly higher than that in RF-negative or ACPA-negative RA. Levels of sLOX-1 in the patients with remission significantly lower than those with moderate disease activity. In the subgroup of patients who were not achieving Boolean-based remission, sLOX-1 level in RF-positive or ACPA-positive RA were significantly higher than that in RF-negative or ACPA-negative RA. In contrast, in the subgroup of patients who were achieving Boolean-based remission, the levels of sLOX-1 in ACPA-positive RA were not significantly higher than that in ACPA-negative RA. Conclusions: These results suggest that the levels of sLOX-1 in the patients who are not achieving remission, especially ACPA-positive RA, increase to reflect disease activity. Therefore, sLOX-1 levels may be useful to evaluate the therapeutic effects of the anti-cytokine therapies. References: Sawarura T, et al. Nature 1997; 386 Nakagawa T, et al. Arthritis Rheum 2002; 46, 2486-94. Kakimuma T, et al. Arthritis Rheum 2004; 50, 3495-503. Ishikawa M, et al. Arthritis Rheum 2012; 64, 1024-34. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2628